Review of sustainable service-based business models in the Chinese truck sector - Pallaro, Estelle; Subramanian, Nachiappan; Abdulrahman, Muhammad D.; Liu, Chang; Tan, Kim Hua (Elsevier, 2016)
Growth of global sales of new trucks in emerging economies is substantial however, in China the growth of sales is expected to be only 1% for 2014–2024. The limited sales growth forecast and an intense market competition make it imperative for truck manufacturers in China to diversify their revenue earnings through service-based business models for the Chinese market. Typically, Chinese service based business models need to be sustainable by considering environmental and social factors in the manufacturer’s business model. This paper reviews existing product–service systems (PSS) and service-based business models in the automotive sector to identify how truck manufacturers could reorient their current business model with respect to the Chinese context to enhance customer satisfaction, profitability and sustainability. The analysis indicates that most of the studies in the automotive sector have focused on product-oriented or use-oriented business models with respect to car segment specifically in the developed markets. Besides, sustainability issues related to vehicle end-of-life management are rarely considered. Our findings suggest that the Chinese truck sector needs an integrated result-oriented PSS business model which could be implemented in other developing countries.